Ima Genome - f14 Draft Genome Sequences of Penicillium Roqueforti, Fusarium Sororula, Chrysoporthe Puriensis, and Chalaropsis Populi - Levican-Jaque, G; Chavez-Rosales, R; Tello-Reyes, M; Valdes-Parra, N; Gil-Duran, C (BioMed Central Ltd, 2021)
Draft genomes of Penicillium roqueforti, Fusarium sororula, Chalaropsis populi, and Chrysoporthe puriensis are presented. Penicillium roqueforti is a model fungus for genetics, physiological and metabolic studies, as well as for biotechnological applications. Fusarium sororula and Chrysoporthe puriensis are important tree pathogens, and Chalaropsis populi is a soil-borne root-pathogen. The genome sequences presented here thus contribute towards a better understanding of both the pathogenicity and biotechnological potential of these species. © 2021, The Author(s).